Multimedia Interaktif Sebagai Media Informasi Mengenai Pengenalan Energi Alternatif - Jaenal Arifin; M. Rizky Fadhlillah (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2017)
Alternative energy is an alternative natural resource that is used for various daily necessities in Indonesia, the information about alternative energy is very minimal because not many facilities or media that discuss it so that students and the general public do not know what alternative energy and its benefits. Therefore the use of interactive multimedia is a solution that can solve the problem of lack of such information. The purpose of making interactive multimedia is to provide information and introduction about alternative energy especially those that have been developed because of alternative energy numbers continue to grow due to many innovations from the development of alternative energy that already exists. In addition to being interactive, the media also contains an explanation of the development of alternative energy for the future so that this media does not become an outdated medium and can serve as a tool to educate about the utilization of alternative energy. The conclusion of the research conducted based on the problems that have been solved by making interactive multimedia can be said to be good and make the user interested to use it as a means of introduction of alternative energy and its development.